(untitled) (LEARNing Landscapes, 2017)
This paper is based on a three-year study that has a dual purpose: firstly, to create a program to attend to the health and wellness of Aboriginal children and youth, and secondly, to narratively inquire into the experiences of the children and youth who participate in the wellness program. In an attempt to disrupt intervention type models that position Aboriginal youth as at-risk, or in-deficit, we pose questions around how wellness programming and research begin in different commitments when we see Aboriginal youth as knowledge holders.